A novel industrial waste filler brake pads - Alida, Abdullah; Che Mohd Ruzaidi, Ghazali, Assoc. Prof.; Mohd Mustafa Al Bakri, Abdullah; Kamarudin, Hussin, Prof. Dr. (Universiti Sains Malaysia, 2013)
The team has won gold medal at National Research and Innovation Competition (NRIC) 2012, 17th - 19th July 2012 was held at Dewan Utama Pelajar, located at USM Main Campus, Penang, Malaysia.